Treatment and Prevention of Transmissive Veneric Sarcoma in Dogs - Yulchiyev Jasurbek Bakhodirovich; Dilmurodov Nasriddin Bobokulovich (Genius Journals, 2022)
Canine transmissible venereal tumour (CTVT) is a contagious venereal tumour of dogs, commonly observed in dogs that are in close contact with one another, or in stray and wild dogs that exhibit unrestrained sexual activity. CTVT represents a unique, naturally transmissible, contagious tumour, where the mutated tumour cell itself is the causative agent and perpetuates as a parasitic allograft in the host. Clinical history, signalment and cytological features are often obvious for establishing a diagnosis though biopsy and histological examination may be needed in atypical cases. Most cases are curable with three intravenous injections of cyclophosphan at weekly intervals. The role of stray and wild dogs makes the disease difficult to control and necessitates sustained animal birth control in stray dogs along with prompt therapy of the affected dogs. This review captures the manifold developments in different areas embracing this fascinating tumour, including its biology, diagnosis and therapeutic alternatives
Keywords: diagnosis; fascinating; including